Forestry in West Bengal - Pal, N. (Indian Forester, 1954)
Forest conservancy in the state of West Bengal dates back to 1864. In the present organizational set up there are, in addition to the head of the Directorate, 2 Conservators’ Circles, 14 Territorial and 5 Non-territorial Divisions. Eight distinct formations of forest occur. The principal timber species is Shorea robusta. The area of the state is 30,775 sq. miles, while the area under forest is 4.413 sq. miles, the proportion of forest thus being 14%. All areas under forest are worked either under Working Plans or Working Schemes.